Analisis Faktor-Faktor Yang Menyumbang Kepada Penglibatan Politik Dalam Kalangan Penduduk Pulau Pinang (Sains Humanika, 2017)
Political participation is one of the fundamental principles of democracy, without which any nation with such system will cease to exist. There are many factors influencing political participation of an individual in a country. Hence this research aims to understand the influence of the level of media usage (i.e. television, radio, newspaper and internet), interest, attitude, general knowledge towards politics and age on political participation through the mediating role of interpersonal discussion, utilizing the Differential Gains Model. A survey involving 386 registered voters in Penang, Malaysia was conducted. The survey discovered that interest in and general knowledge on politics significantly influenced the level of the respondents’ political participation. None of any media factors, attitudes toward politics and age was found to affect political participation. Consistent with the Model of Differential Gains, interpersonal discussion on politics significantly mediated the relationships between level of media usage (namely radio and newspaper) and general knowledge on politics; and political participation. The study summarised that interpersonal discussion on political issues with friends and family members is more vital to increase people’s involvement in local politics as compared to mass media.
Keywords: Differential Gain Model; Interpersonal discussion; mass media usage; political participation